INCREASING COMPETITIVE ADVANTAGE SUSTAINABILITY THROUGH STRATEGIC ALLIANCE - Zulfan; Putri Anggraini; Rini Mardiana; Putri Anjani Rahayu (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
This study aims to find out and examine the empirical description of the strategic problems faced and the strategies implemented in response to future human resource development needs as well as the Strategic Alliances conducted by STP to respond to global competition. Sustainable Competitive Advantage , This study uses a naturalistic qualitative approach, with descriptive methods and case studies, with data collection techniques using interviews, observation and document studies. The sampling technique used is purposive. Data analysis was carried out through the process of displaying data, reducing data and verifying data through a triangulation process. Sustainable Competitive Advantage , This study uses a naturalistic qualitative approach, with descriptive methods and case studies, with data collection techniques using interviews, observation and document studies. The sampling technique used is purposive. Data analysis was carried out through the process of displaying data, reducing data and verifying data through a triangulation process.